Transfusion Medicine Equations Made Internet Accessible. (21st September 2018) - Charifa, Ahmad; Ryder, Alex; Cheng, Caleb; Tormey, Christopher; Hauser, Ronald
Abstract: Objectives: Evidence-based transfusion medicine practice involves mathematical equations application. These equations guide blood products dosage (eg, plasma, cryoprecipitate), allow for fluid volumes calculation (eg, total body fluid volume, red cell volume, and plasma volume), and inform treatment decisions (eg, corrected count increment for the determination of platelet refractoriness). While undoubtedly useful, the growing number and complexity of transfusion medicine equations often conflicts with the time and resources available for their implementation. Methods: Transfusion medicine and apheresis information sources (ie, textbooks, manuscripts, and electronic guidelines) were reviewed by the project investigators for the most up-to-date versions of equations applicable broadly to pediatric and adult clinical practice. After several meetings, 20 equations were identified for inclusion based on their perceived impact and frequency of use in daily medical practice. Results: Equations were divided into five categories: (1) basic blood volume estimates (ie, whole blood/plasma/RBC volume calculations for adults, children, and neonates; n = 8), (2) general transfusion medicine management (platelet transfusion-corrected count increment equations and donors to screen in the setting of RBC alloantibodies; n =3), (3) component dosing (ie, for plasma and cryoprecipitate dosing; n =2), (4) perinatal and maternal transfusion medicine management (ie, volumes for intrauterine transfusion, neonatal partial exchange calculations, and Rh immune globulin dosing; n = 3), and (5) apheresis management (ie, therapeutic plasma exchange volume removal, sickled RBC exchange volumes, and stem cell/donor lymphocyte collection procedures; n = 4). Equations were subsequently loaded into a template containing the abstract equation with details about background, basic facts, and limitations of each equation. Equations were subsequently validated with theoretical numbers, and templates with embedded equations were communicated to programmers to be uploaded to an online calculator. Conclusion: Clinicians can now utilize reputable and highly visible online source to access these transfusion medicine equations at any time with an Internet-enabled phone, PC, and tablet.